EP628 Recurrence rate after laparoscopic surgery versus laparotomy for early stage endometrial cancer. (1st November 2019) - Sumak, R; Sibli, I; Cokan, A; Pakiz, M
Abstract : Introduction/Background: To explore long term recurrence rate of patients with early stage endometrial cancer according to the type of surgery (laparoscopy vs. laparotomy). Methodology: The retrospective analysis included all 144 consecutive early stage patients operated by laparotomy between years 2001 and 2006 and 61 consecutive patients operated by laparoscopy between years 2008–2013, to have at least 5 years of follow up. The general data were compared between patients being operated laparoscopicaly and through laparotomy. Then all patients who had recurrence of the disease were studied in details regarding the location of the recurrence and the risk factors of the primary disease. Results: Six patients in laparotomy (6/144 [4.2%]) and three patients in the laparoscopy group (3/61 [4.9%]) did not come to follow-up after surgery. Patient characteristics and results are presented in tables 1 and 2. Three (33.3%) patients after laparotomy reccured with not-expected distant metastasis and one (50%) after laparoscopy. All four of them had low/intermediate risk disease. Althought more patients after laparotomy received adjuvant radiotherapy (change of guidelines) and more lymph nodes were removed through laparoscopy, it did not influence the recurrence rate. Conclusion: We did not find the difference in recurrence rate or location of recurrence between laparoscopical approach vs. laparotomy in stage I endometrial cancer. Disclosure: Nothing to disclose.